In-situ preparation of Li3V2(PO4)3/C and carbon nanofibers hierarchical cathode by the chemical vapor deposition reaction. (10th January 2016) - Zhang, Rongyu; Yang, Xu; Gao, Yu; Ju, Yanming; Qiu, Hailong; Meng, Xing; Chen, Gang; Wei, Yingjin
Graphical abstract: Abstract: Carbon nanofibers are in-situ prepared in carbon coated Li3 V2 (PO4 )3 by the chemical vapor deposition method. The carbon nanofibers connect the isolated Li3 V2 (PO4 )3 regions thus constructing an efficient conductive network for electrons transportation. In addition, incorporation of the surface carbon coating and carbon nanofibers promotes the electrochemical kinetic properties of the material which improves the electrochemical performance of Li3 V2 (PO4 )3 . In all materials under investigation, the one containing 6.4 wt% carbon nanofibers shows excellent cycle stability resulting in capacity retention of 90.5% after 300 cycles. Moreover, a large discharge capacity of 94.7 mAh g −1 is obtained at the 20C rate highlighting excellent rate capability of the material.